2021
DOI: 10.18502/fem.v6i1.7674
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life and emotional well-being among healthcare workers during the COVID-19 pandemic in Iran

Abstract: Objective: Healthcare workers (HCWs) are among the highest groups impacted by the COVID-19 pandemic. This study aimed to analyze professional quality of life (ProQOL) and its association with emotional well-being in HCWs during the pandemic. Methods: This cross-sectional study was conducted on HCWs being in close contact with COVID-19 patients in Iran. The questionnaires assessing ProQOL, emotional well-being, and demographic and occupational characteristics were recruited via email or social media. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 0 publications
1
14
1
11
Order By: Relevance
“…Also, this study highlighted the association between healthcare workers' work experience and BO, a relationship not observed in our study. 27 Conversely, a study in Egypt reported high levels of BO among physicians, which contrasts with our findings. Nevertheless, associations between sex, marital status, BO and CS resembled our study's findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, this study highlighted the association between healthcare workers' work experience and BO, a relationship not observed in our study. 27 Conversely, a study in Egypt reported high levels of BO among physicians, which contrasts with our findings. Nevertheless, associations between sex, marital status, BO and CS resembled our study's findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Two surveys of frontline healthcare workers, conducted in the wake of the first wave of the pandemic reported similar findings. A survey of 705 healthcare workers in Iran who were working in close contact with COVID-19 patients found that almost all (98.3%) showed moderate to high levels of CS with the majority (76.6%) showing a moderate level of BO (Azizkhani, Heydari et al 2021). In Spain, a survey of 973 healthcare professionals, conducted after the first wave of the pandemic to assess the situation when the pressure on services and work overload had eased, (Dosil, Ozamiz-Etxebarria et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found leadership, information provision and access to workplace resources as mediating factors in improving emergency preparedness among redeployed nurses [25,48,49]. The issue of how best to support redeployed healthcare workers has attracted extensive attention worldwide [50][51][52][53]. NHS England and NHS Improvement published national guidance on key considerations for the safe redeployment of staff and deployment of those joining the NHS temporarily to support the existing workforce [54].…”
Section: Discussionmentioning
confidence: 99%